Sex- and Development-Dependent Responses of Rat Microglia to Pro- and Anti-inflammatory Stimulation - Lively, Starlee; Wong, Raymond; Lam, Doris; Schlichter, Lyanne C. (Frontiers in Cellular Neuroscience, 2018)
Addressing potential sex differences in pre-clinical studies is crucial for developing therapeutic interventions. Although sex differences have been reported in epidemiological studies and from clinical experience, most pre-clinical studies of neuroinflammation use male rodents; however, sexual dimorphisms in microglia might affect the CNS inflammatory response. Developmental changes are also important and, in rodents, there is a critical period of sexual brain differentiation in the first three weeks after birth. We compared rat microglia from sex-segregated neonates (P1) and at about the time of weaning (P21). To study transitions from a basal homeostatic state (untreated), microglia were subjected to a pro-inflammatory (IFNγ+TNFα) or anti-inflammatory (IL-4) stimulus. Responses were compared by quantifying changes in nitric oxide production, migration, and expression of nearly 70 genes, including inflammatory mediators and receptors, inflammasome molecules, immune modulators, and genes that regulate microglial physiological functions. No sex differences were seen in transcriptional responses in either age group but the IL-4-evoked migration increase was larger in male cells at both ages. Protein changes for the hallmark molecules, NOS2, COX-2, PYK2 and CD206 correlated with mRNA changes. P1 and P21 microglia showed substantial differences, including in expression of genes related to developmental roles. That is, P21 microglia had a more mature phenotype, with higher basal and stimulated levels of many inflammatory genes, while P1 cells had higher expression of phagocytosis-related molecules. Nevertheless, cells of both ages responded to IL-4 and IFNγ+TNFα. We examined the Kv1.3 potassium channel (a potential target for modulating neuroinflammation) and the Kir2.1 channel, which regulate several microglia functions. Kv1.3 mRNA (Kcna3) was higher at P21 under all conditions and male P21 cells had higher mRNA and Kv currents in response to IFNγ+TNFα. Overall, numerous transcriptional and functional responses of microglia changed during the first three weeks after birth but few sex-dependent changes were seen.